Gramaticalização da construção 'é claro que': padrões na fala e na escrita. - Fortilli, Solange [UNESP]; Gonçalves, Sebastião Carlos Leite [UNESP] (My University, 2013)
In this paper, we investigate the grammatical construction “é claro (que)”, which is characterized as a matrix clause. As it is produced, an argumentative clause is added to the matrix clause in subject position. We analyze oral speech and writing data of contemporary Portuguese and show that the grammatical construction undergoes processes of change, which are identified by desentencialization clauses and grammaticalization process. In addition, by analyzing parameters such as the position of grammatical construction, the presence of copulation and the use of a complementizer, we show that the absence of copulation and a complementizer in the matrix leads to a reduced clause, i.e., a monoclause, and a categorical change of the matrix adjective, which plays the role of functioning adverb.

Neste trabalho, tratamos da construção “é claro (que)”, que se configura como oração matriz, na qual se encaixa uma oração completiva em posição argumental de sujeito. Com base em amostras de fala e de escrita do português contemporâneo, apresentamos evidências de que essa construção vem passando por processos de mudança identificados com a gramaticalização e a dessentencialização de orações. Analisando parâmetros como posição da construção, presença de cópula e presença de complementizador, mostramos que a ausência de cópula e de complementizador na matriz leva à redução do complexo oracional, que, de bioracional, passa a mono-oracional, e à alteração categorial do adjetivo matricial, que passa a ter funcionamento adverbial.
Grammaticalization of the construction “é claro que”: patterns in speech and writing
Keywords: gramaticalização; oração subjetiva; oração matriz